2021
DOI: 10.1021/acs.iecr.1c03669
|View full text |Cite
|
Sign up to set email alerts
|

Green Fabrication of High-Performance, Lignosulfonate-Functionalized, and Reduced-Graphene Oxide Styrene–Butadiene Rubber Composites

Abstract: The preparation of high-performance graphene/rubber composites by green compounding methods is one of the dominant trends in exploiting and extending the applications of graphene in the rubber industry. A novel strategy is demonstrated here for fabricating a functionalized reduced-graphene oxide (SRGO) aqueous dispersion employing sodium lignosulfonate (SLS) as the stabilizer and ascorbic acid as the reductant. Furthermore, the SRGO was introduced into a styrene−butadiene rubber (SBR) matrix via the green late… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…After aging at 100 • C for 672 h, the tan δ at 20 • C reduced by 20.6% compared to the unaged sample. These experimental results showed that the aging of rubber composites affected the mutual mobility of rubber molecular chains, leading to reduced toughness and damping performance [45]. Consequently, the deterioration of the EPDM composites within the spacer diminished energy absorption during wire swinging and hindered the wire dancing control.…”
Section: Dynamic Damping Of Rubber Compositesmentioning
confidence: 95%
“…After aging at 100 • C for 672 h, the tan δ at 20 • C reduced by 20.6% compared to the unaged sample. These experimental results showed that the aging of rubber composites affected the mutual mobility of rubber molecular chains, leading to reduced toughness and damping performance [45]. Consequently, the deterioration of the EPDM composites within the spacer diminished energy absorption during wire swinging and hindered the wire dancing control.…”
Section: Dynamic Damping Of Rubber Compositesmentioning
confidence: 95%